Use of waste optical disc in concrete to promote Sustainable development in construction industry - Chee Kang, Neo; Osman, Mohammad Hairi; Adnan, Suraya Hani (Penerbit Uthm, 2018)
In recent years, happening of few catastrophic natural disasters have raise the awareness of public on environmental issue that the Earth is getting sick. Preservation and conservation of environment started to be given concern by people all over the world. Sustainable development is becoming the trench of construction industry nowadays and many countries start emphasizing on application of green practices in building construction.